PENCEGAHAN KECURANGAN DALAM ORGANISASI PEMERINTAHAN - Dita Putri Noviani; Yudhanta Sambharakreshna (Master of Accounting Universitas Trunojoyo Madura, 2014)
The purpose of this research is to examine and analyze the effect of the role of the internal auditor, the auditor ethical behavior, whistleblower and hotline to the prevention of fraud in establishing government organizations. The population in this research is in The Development Finance Comptroller (BPKP) auditors representative of East Java province. The sampling technique used is purposive sampling. The samples of this research are 66 samples.The results of this research indicated that the first, the role of internal auditors have a significant effect on the prevention of fraud in government organizations. Secondly, ethical behavior of auditors have a significant effect on the prevention of fraud in government organizations. Third, whistleblower and hotline have a significant effect on the prevention of fraud in government organizations.